INCORPORATION OF A TWO-FLUX MODEL FOR RADIATIVE HEAT TRANSFER IN A COMPREHENSIVE FLUIDIZED BED SIMULATOR PART II: NUMERICAL RESULTS AND ASSESSMENT - Rabi, J. A.; de Souza-Santos, M. L. (Revista de Engenharia Térmica, 2003)
As shown in the first part of this paper, equations and considerations for a preliminary attempt to improve the treatment for radiative heat transfer of a previous comprehensive simulation program were presented. For that, the two-flux radiative heat transfer model was applied. In this second part, the new version of that program was tested against steady-state operations of real equipment. Numerical simulations were carried for two different fluidized-bed reactors: a coal-fed boiler and a wood-fed gasifier. Computational results obtained with that new version were compared with those obtained with the previous simulator version. Then, both sets of results were also compared with real operational data. Special attention was paid to the temperature profiles of each particle species present in the bed section carbonaceous, limestone and inert as well as to the radiative heat transfer rates between these solids. Effects on the temperature profiles of the gas phases emulsion and bubbles and on the equipment performance parameters were also investigated. Improvements related to the incorporation of two-flux model are assessed and discussed. New developments and extensions of this approach are indicated.